Precursor-driven nucleation and texture control governing resistivity in low-temperature In2O3 films - Kim, Tae-Kyung; Gwoen, Ji-Hyun; Han, Ju-Hwan; Kim, Hae-Dam; Kim, Ji Min; Kim, Tae-Heon; Kim, Sang-Hyun; Song, Ki-Cheol; Park, Jin-Seong (Elsevier BV, 2025)
Achieving low resistivity (rho) and sufficient carrier mobility (mu) in In2O3 thin films deposited by plasma-enhanced atomic layer deposition (PEALD) at <= 100 degrees C remains challenging due to limited crystallinity and grain-boundary scattering. This study demonstrates that precursor-controlled nucleation-rather than film thickness or bulk crystallinity-is the key factor governing carrier mobility and resistivity. Two indium precursors, DIP3 (MeIn(Pr)(2)NMe) and DIP4 (InMe3(THF)), were employed to investigate the growth, structure, and optoelectronic properties of In2O3 films 30-100 nm thick. Characterization used grazing-incidence XRD, XPS, spectroscopic ellipsometry, UV-Vis, and van der Pauw Hall measurements. Films grown with DIP3, which exhibits a lower nucleation density, maintained a stable (222)/(400) texture up to 80 nm and achieved rho = 1.1 x 10(-)(3) Omega cm and FoM = 1.5 x 10(-)(3) Omega(-)(1) without post-annealing. In contrast, DIP4 films showed an earlier onset of random orientation and a pronounced mobility decline beyond 50 nm, attributed to higher nucleation density. Increasing the number of DIP3 dosing pulses per ALD cycle raised the growth per cycle (GPC) by 0.04 & Aring;/cycle and increased resistivity to 6.8 x 10(-)(3) Omega cm, accompanied by a rise in the (411) peak intensity. These results confirm that accelerated nucleation promotes random grain orientation, thereby increasing resistivity and reducing mobility. All films exhibited > 80 % transmittance in the visible range. Overall, these findings highlight that reducing resistivity in low-temperature PEALD requires controlling nucleation and crystallographic texture rather than simply increasing film thickness.